ANALISIS YURIDIS PENYELESAIAN SENGKETA PERBANKAN SYARIAH PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR : 93/PUU-X/2012 - Ulul Albab; Umam, Syafiul; Nasiruddin, Muhammad (TIJAROTANA : Jurnal Ekonomi Dan Bisnis Syariah, 2021)
The problem of banking dispute resolution arises after the birth of Law Number 8 of 2008 concerning Sharia Banking, precisely in Article 55 paragraph (2) which in explaining gives the choice to the banking dispute parties to resolve the problem of Islamic banking disputes based on the contents of the contract that has been done, namely through deliberations, banking mediation, the Arbitration Board, and the General Judiciary. Juridically reduce Law Number 3 of 2006 concerning Religious Courts which gives the authority of the Religious Courts in resolving Islamic economic disputes that gives rise to the dualism of the Court's authority, namely the Religious Courts and General Courts. In the Constitutional Court Decision Number 93 / PUU-X / 2012 states that Article 55 Paragraph (2) of the Sharia Banking Law, causes legal uncertainty that is contrary to Article 28D Paragraph (1) of the 1945 Constitution concerning legal certainty. The research method is library research, namely research that studies and examines theories, and ideas, with a normative approach that aims to provide a systematic exposition of the rule of law governing a particular legal field, analyzing between legal relationships with or with others and explain the difficult parts to understand from a certain law. This study analyzes the settlement of Sharia Banking disputes Post Constitutional Court Ruling Number: 93 / PUU-X / 2012 and the legal implications of the decision of the Constitutional Court Number: 93 / PUU-X / 2012 on Sharia Banking dispute settlement.